Management Practice in Production - Thomas Triebs; Subal C. Kumbhakar (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2012)
In this paper we account for observed management practice in the estimation of aproduction function. In our model management practice is observable and we allow it toaffect output directly (neutral shift) and indirectly by affecting input productivity. Thisformulation gives us a semiparametric smooth coefficient model. Empirically, we findthat estimates of unobserved (in)efficiency do not correlate highly with observedmanagement. We also find that management affects output both directly and indirectlyvia all factors of production, i.e., the productivity effect of management is non-neutral.Finally, we find that the indirect effects of conventional inputs vary with management.
Keywords: D24; C14; M11; 330; Management practice; production functions; semiparametric model; Management; Produktionsfunktion; Produktionsfaktor; Produktivität; Theorie; Welt